Atovaquone-Proguanil in Combination With Artesunate to Treat Multidrug-Resistant P. falciparum Malaria in Cambodia: An Open-Label Randomized Trial. (4th September 2019) - Wojnarski, Mariusz; Lon, Chanthap; Vanachayangkul, Pattaraporn; Gosi, Panita; Sok, Somethy; Rachmat, Agus; Harrison, Dustin; Berjohn, Catherine M; Spring, Michele; Chaoratanakawee, Suwanna; Ittiverakul, Mali; Buathong, Nillawan; et al.
Abstract: Background: Recent artemisinin-combination therapy failures in Cambodia prompted a search for alternatives. Atovaquone‐proguanil (AP), a safe, effective treatment for multidrug-resistant Plasmodium falciparum ( P.f. ), previously demonstrated additive effects in combination with artesunate (AS). Methods: Patients with P.f. or mixed-species infection (n = 205) in Anlong Veng (AV; n = 157) and Kratie (KT; n = 48), Cambodia, were randomized open-label 1:1 to a fixed‐dose 3-day AP regimen +/-3 days of co‐administered artesunate (ASAP). Single low-dose primaquine (PQ, 15 mg) was given on day 1 to prevent gametocyte-mediated transmission. Results: Polymerase chain reaction–adjusted adequate clinical and parasitological response at 42 days was 90% for AP (95% confidence interval [CI], 82%–95%) and 92% for ASAP (95% CI, 83%–96%; P = .73). The median parasite clearance time was 72 hours for ASAP in AV vs 56 hours in KT ( P < .001) and was no different than AP alone. At 1 week postprimaquine, 7% of the ASAP group carried microscopic gametocytes vs 29% for AP alone ( P = .0001). Nearly all P.f. isolates had C580Y K13 propeller artemisinin resistance mutations (AV 99%; KT 88%). Only 1 of 14 treatment failures carried the cytochrome bc1 (Pfcytb) atovaquone resistance mutation, which was not present at baseline. P.f. isolates remained atovaquone sensitive in vitro but cycloguanil resistant, with a triple P.f. dihydrofolate reductase mutation. Conclusions: Atovaquone-proguanil remained marginally effective in Cambodia (≥90%) with minimal Pfcytb mutations observed. Treatment failures in the presence of ex vivo atovaquone sensitivity and adequate plasma levels may be attributable to cycloguanil and/or artemisinin resistance. Artesunate co-administration provided little additional blood-stage efficacy but reduced post-treatment gametocyte carriage in combination with AP beyond single low-dose primaquine. Abstract : Despite no additional asexual-stage malaria efficacy, adding artesunate (AS) to 3-day atovaquone-proguanil (AP) treatment reduced post-treatment gametocyte carriage in Cambodia. AP monotherapy retained marginally > 90% efficacy against multidrug resistant P. falciparum . Only one recurrent isolate harbored Pfcytb atovaquone resistance mutation.